Effect Size Model Inquiry Based Learning on the Ability of Pancasila Student Profile - Miftachul Amri; Aloisius Harso; Ni Desak Made Santi Dwyarthi; Unpris Yastanti; Mohammad Edy Nurtamam (AKADEMI TEKNIK ADI KARYA, 2024)
The purpose of this study was to determine the effect of the size of the inquiry-based learning model on the ability of the student profile of Pancasila students. This type of research is quantitative research with a meta-analysis approach. Data sources come from 10 journals published 2020-2024. The process of searching for data through google scholar, mendeley, ScienceDirect, ERIC and Taylor of Francis. Data selection process using PRISMA 2020 method. Inclusion criteria are research must be experimental methods, research comes from national and international journals indexed by SINTA and Scopus, research must be related to research variables, research subjects of elementary, junior high and high school students, and research has complete data to calculate the value of effect size. Data analysis is calculating the effect value of each study with the help of Microsoft Excel 2020. The results of the study concluded that the inquiry-based learning model had a significant influence on the ability of the student profile of Pancasila students with an average effect size value of 0.806 with high effect size criteria. This study provides important information for teachers to implement inquiry-based learning models on the ability of student profiles of Pancasila students